Research Trends Mathematics Concepts on Pre-Service Mathematics Teachers: A Bibliometric Analysis Using Vosviewer From 2017 To 2022 - Sugiarni, Rani; Herman, Tatang; Suryadi, Didi; Prabawanto, Sufyani; Inayah, Sarah (Universitas Suryakancana, 2023)
Preparing qualified teacher candidates also helps to create a sustainable education system, therefore, the preparation of teacher candidates should be a priority for any education system that wants to achieve success and sustainability. Some research on prospective mathematics teachers has developed rapidly. This study aims to investigate: 1) what is the performance analysis of publication and citation-related metrics and their trends from pre-service teacher mathematics studies, and 2) what is the science mapping and network analysis of citation analysis, authorship partner analysis, and word partner analysis from pre-service teacher mathematics studies. A research method is a bibliometric approach using the Scopus database with two search keywords namely